An Examination of the Instructional Partner Role of a Media Specialist - Harrison, Melissa R. (Valdosta State University, 2005)
The purpose of the research was to examine how collaboration of a media specialist with teachers and students for using an online media catalog influenced teacher attitudes and student attitudes toward the media specialist as an instructional partner. In addition, the study was conducted to determine how teachers and students utilized an online media catalog for developing and completing class assignments. The media specialist collaborated with teachers to design instruction and trained students to use the online media catalog. This study included surveys, observations, interviews, and questionnaires. Students created projects that focused on various subject areas. Assignments were designed to allow students to search the automated media catalog to gather materials needed to complete the assigned project. Findings suggested that a collaboration between the media specialist and teachers advanced the role of the media specialist as instructional partner; that students believed that learning was better when teachers and media specialists work together; and that teachers and students saw the importance of using the online media catalog with classroom assignments. The results of the study were communicated to the learning community through a meeting with teachers and administrators. That meeting supported continuation of training students to use the online media catalog and fostered a collaborative environment for interested teachers and media specialist.
Keywords: media specialist; online media catalog; instructional partner; School librarians; Media programs (Education)